Pencegahan 3 Dosa Pendidikan melalui Character Building berbasis Kearifan Lokal Bali: Tat Twam Asi - Astutik, Windu; Kiswara, Komang Agus Triadi; Dewi, Putu Ratna Suprima; Widayati, Kurniasih (Jurnal SOLMA, 2025)
Background: Problems that arise because of bullying and sexual violence not only threaten the victim physically, but also psychologically. These three educational sins can be an obstacle to creating a good learning environment and cause trauma for children who are victims so that they can interfere with academic achievement and success. Preventing the 3 dosa besar pendidikan by establishing youth that is given peer educator training, and character education using the Tat Twam Asi concept approach. Method: This activity was carried out for 3 months, namely July to September 2024, involving partners, namely teachers and students of SMA Negeri 3 Denpasar and the activity implementation team consisting of the PKM Proposing Team, KPAD Bali Province, Psychologists and religious leaders. Results: The results of this activity were that 20 assigned students were selected, there was an increase in knowledge to 95% after socialization regarding the 3 major sins in education, there were 95% of students' attitudes and behavior according to the Tat Twam Asi concept and 90% of the task force members had the skills to prevent, detect and handle adolescent mental health problems related to the 3 dosa besar Pendidikan. Conclusions: Based on the increase in knowledge and skills shown by the posttest value, which is greater than the pretest value, it can be concluded that socialization, character education and peer educator training are quite effective in increasing knowledge and skills.